ANALISIS JEJARING SOSIAL PADA KOORDINASI KLASTER KESEHATAN DALAM TANGGAP DARURAT BENCANA BANJIR BANDANG GARUT 2016 - Dina Adlina Amu; Tri Budhi Edhi Soesilo; Tata Kustana (Republic of Indonesia Defense University, 2019)
Disaster is the real threat for national security. Flash flood in Garut 2016 was the biggest disaster in West Java during 2016 as well as the worst flash floods in history in Garut regency. Health service efforts during the emergency response period should be undertaken to protect human security. Lack of coordination becomes one of obstacles in the health service efforts during the emergency response period of flash flood in Garut 2016. Therefore, this study aims to see the structure and the key actor of inter-agency coordination of health cluster in emergency response of flash flood Garut 2016. Research design of this study is mix method that used social network analysis as a method of analysis in quantitative approach and Miles & Huberman analysis as a method of analysis in qualitative approach. The study involved 32 respondents who represented 29 health cluster institutions consisting of government, NGO, professional and private organization. The results showed the type of structure of inter-agency coordination of health cluster during the emergency response of flash flood Garut 2016 is lead agency with network density 3%. The problem is the coordination chain is quite long because it requires 3-6 liaison agencies, but Garut regency does not have contingency plans that can arrange it. The results also showed that the key actor of inter-agency coordination of health cluster during emergency response in flash flood Garut 2016 was Health Office of Garut regency. Therefore, Health Office of Garut Regency needs to make an MoU with NGOs to help the government as a liaison agency in the coordination network. Local governments, communities and private sector should also work together in making contingency plans for floods in Garut for future convenience.